2013
DOI: 10.15623/ijret.2013.0203013
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Plant Without Soil - Hydroponics

Abstract: With the advent of civilization, open field/soil-based agriculture is facing some major challenges; most importantly decrease in per capita land availability. In 1960 with 3 billion population over the World, per capita land was 0.5 ha but presently, with 6 billion people it is only 0.25 ha and by 2050, it will reach at 0.16 ha. Due to rapid urbanization and industrialization as well as melting of icebergs (as an obvious impact of global warming), arable land under cultivation is further going to decrease. Aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…To prevent the development of hypoxia, additional aeration needs to be provided for plants grown in PEG-containing medium. For this, air is continuously supplied by pumps through silicone tubes connected to the culture vessels [71]. Although this approach can be easily established for larger plants (as it was done in our lab with B. napus ; Figure 2B [72]), small model plants like Arabidopsis, typically grown in small vessels on large scale for highly replicated biological experiments, cannot be supplied with air individually and are typically grown under hypoxic conditions [73].…”
Section: Experimental Models Of Drought Stressmentioning
confidence: 99%
“…To prevent the development of hypoxia, additional aeration needs to be provided for plants grown in PEG-containing medium. For this, air is continuously supplied by pumps through silicone tubes connected to the culture vessels [71]. Although this approach can be easily established for larger plants (as it was done in our lab with B. napus ; Figure 2B [72]), small model plants like Arabidopsis, typically grown in small vessels on large scale for highly replicated biological experiments, cannot be supplied with air individually and are typically grown under hypoxic conditions [73].…”
Section: Experimental Models Of Drought Stressmentioning
confidence: 99%
“…Hydroponics is the soil-less cultivation of plants using mineral nutrient solutions (Sardare and Admane 2013). In this method, nutrients are fed directly to the roots.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on cytotoxicity caused by substances such as agrochemicals and secondary metabolites in plants (BALIGA et al, 2011;MOREIRA et al, 2014;FERREIRA et al, 2016;SANTOS et al, 2016); however, little is known about the toxicity of the nutrient solutions used in hydroponic crops. This may be directly related to the fact that the morphology and composition of plant metabolites in artificial environments can be accurately adapted to the physical and chemical conditions of this environment (MIYAGI et al, 2017;SARDARE;ADMANE, 2013). Macedo et al (2014) suggest that mitotic indices, whether higher or lower than a negative control, indicate the changes in root growth and development caused by nitrogen, which may also be detrimental to cells and lead to disordered cell proliferation and eventual tumor formation.…”
Section: Cytotoxic and Genotoxic Analysismentioning
confidence: 99%